Kierkegaard's journals and notebooks. - Kierkegaard, Søren, 1813-1855 (Princeton University Press, 2008)
Søren Kierkegaard (1813-55) published an extraordinary number of works during his lifetime, but he left behind nearly as much unpublished writing, most of which consists of what are called his ""journals and notebooks."" Volume 2 of this 11-volume edition of Kierkegaard's Journals and Notebooks includes materials from 1836 to 1846, a period that takes Kierkegaard from his student days to the peak of his activity as an author. In addition to containing hundreds of Kierkegaard's reflections on philosophy, theology, literature, and his own personal life, these journals are the seedbed